Plasma Bleomycin Concentrations during Electrochemotherapeutic Treatment of Fibropapillomas in Green Turtles Chelonia mydas. Issue 2 (17th May 2019) - Donnelly, Kyle A.; Papich, Mark G.; Zirkelbach, Bette; Norton, Terry; Szivek, Anna; Burkhalter, Brooke; Impellizeri, Joseph A.; Stacy, Nicole I.
Abstract: Fibropapillomatosis of sea turtles is traditionally treated with surgical debulking techniques that are often associated with prolonged healing and tumor recurrence. Electrochemotherapy was recently described for green turtles Chelonia mydas and can be an alternative to surgery and even general anesthesia. The objectives of this study were to replicate an electrochemotherapy protocol from a previous report and add plasma bleomycin analysis to the treatment. After bleomycin injection into similarly sized tumors of two green turtles and immediate electroporation at two time points, plasma bleomycin reached detectable concentrations that were considerably lower than those found in human studies. At 3 months posttherapy, no healing complications or recurrences were encountered and only scar tissue remained. This study adds further support that electrochemotherapy with bleomycin has the potential to be used as an effective alternative treatment for this complex disease.